WASPAS METHOD FOR CORRELATED RESPONSE OPTIMIZATION DURING DRILLING OF NANO ONIONS STRUCTURED CARBON-REINFORCED POLYMER COMPOSITES - Kesarwani, Shivi; Verma, Rajesh Kumar (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
This study investigates the machinability aspects and parametric optimization during the drilling of Carbon nano onion reinforced polymer (epoxy) nanocomposites. A hybrid module of Principal Component Analysis (PCA) and Weighted Aggregated Sum Product Assessment (WASPAS) technique is explored to achieve the desired machining responses. The proposed module efficiently optimizes the four process parameters, namely, CNO % (Wt.%), Speed (S), Feed (F), and Drill-bit materials (M) (HSS, Carbide, and TiAlN). The study aims to determine the optimum value of the three process responses, i.e., Torque (Tr), Thrust force (Tf), and Surface roughness (Ra), in terms of a single objective function value (Qi). ANOVA is utilized to determine the percentage contribution of each drilling variable. The optimum settings were obtained at CNO Wt.% - 0.5 %, S-1500 rpm, and F-100 mm/min with a TiAlN drill bit. The findings of the hybrid PCA-WASPAS are more feasible (11.596 %) than the conventional WASPAS method.